Infleunce of Body Mass Index (BMI) on Outcome of Colon Cancer in Relationships with Other Clinicopathological Factors - A Mubarak , Ahmad; H Mustaf, Alaa (Diyala Journal of Medicine, 2021)
Background: Colon cancer is the third most common cancer. High (BMI) contributes hazardously for several types of malignancies including colon cancer while the effect of BMI as a prognostic factor is poorly defined. Objective: Demonstrating the influence of increasing (BMI) on colon cancer recurrence. Patients and Methods: Case-control study involved a sample of 312 patients and 131 patients were excluded from this study and only 181 patients of colon cancer are included in the study with stage 2 and 3 who did underwent a surgical operation and received adjuvant chemotherapy recruited from an oncology teaching hospital, Al Jawad oncology center (Alkadhemiya hospital) and Babylon Oncology center. Results: The study involved 181 patients of colon cancer patients with mean age of 56.25 ±11.74years the highest proportion of study patients (90.6%) were aged more than 40yrs with a male to female ratio (1.2:1). Overweight patients constituted 39.2% and obese 23.8% and normal body weight 37%. In this study majority of tumors are ulcerating for about 72.5% and sigmoid and left side colon was the most common site of the tumor in about 53% with stage three is a most common type. Regarding recurrence, 54.1% of study patients have recurrence, and the majority of the 41.8% occurs between 1-3years after primary tumors diagnoses and treatment with a high prevalence of recurrence was seen in obese patients (74.4%) with a significant association between prevalence of recurrence and increasing BMI. In this study, 61.2% of patients with lymphovascular invasion have recurrences of malignancy with significant associations between recurrences and LVIe. Also more than 50% of patient older than 40years got recurrences with significant associations between recurrences with age of patients. In this study we take the effect of each clinicopathological feature on the outcome of colon cancer and then to excluded its effect by logistic regression to see the effect of only BMI on the outcome of colon cancer. Conclusion: Increase body mass index is associated with increase recurrence of colon cancer